Unfolded protein response-related gene regulation in inflamed periodontal tissues with and without Russell bodies. (September 2016) - Seo, Benedict; Coates, Dawn E.; Seymour, Gregory J.; Rich, Alison M.
Highlights: Genes that mitigate ER stress are up-regulated in inflamed RB + tissues. In periodontal inflammation, genes associated with ER stress are down-regulated. HSP70 down-regulation may be implicated in periodontal inflammation. Abstract: Objective: To examine the expression of unfolded protein response (UPR) genes, a set of genes that are activated to assist in protein trafficking and cellular homeostasis when endoplasmic reticulum (ER) stress occurs, in inflamed and uninflamed periodontal tissues, with or without Russell bodies (RB). RB are a histologically apparent extension of the ER that represents an accumulation of abnormal proteins that cannot be secreted or degraded and may serve as a marker of ER stress. Design: Periodontal tissue specimens were collected and categorised histologically based on the presence of inflammation and the quantity of RB. The differential regulation of 84 UPR-related genes was examined by qRT 2 -PCR. Results: UPR genes related to the inositol-requiring ER-to-nucleus signal kinase (IRE)-1 pathway, molecular chaperones and ER quality control were up-regulated in RB + tissues compared with RB − tissues, irrespective of inflammation. Inflamed periodontal tissues showed a marked down-regulation of heat shock protein (HSP)-70 family members. Conclusion: The presence of RB in inflamed periodontal tissues correlated with the expression of a unique set of ER stress-related genes and therefore may serve as a marker of UPR response in periodontal inflammation. Inflamed periodontal tissues showed a marked down-regulation of UPR genes, in particular HSP70. This may be contributory to disease progression in periodontal disease.